1991
DOI: 10.1021/bk-1991-0468.ch019
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Soil Venting Model and Its Applications

Abstract: In-situ soil venting has emerged as a promising remedial technology for soils contaminated with volatile or semi-volatile organics. A three-dimensional numerical model is developed to predict subsurface air pressure and velocity profiles during soil venting. The applications of the model include estimating the zone of influence, air flow rate, and pressure drawdown induced by a venting system. Estimated values of these parameters are needed for system design. The paper provides practical examples of how to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The A/A-D equation method is commonly taken; a review of literature-reported SVE models (Table 1) yielded twenty-two coupled air flow/contaminant transport and removal models [ 7-28], as well as six air flow-only models [29][30][31][32][33][34] based on this approach.…”
Section: Process Performancementioning
confidence: 99%
“…The A/A-D equation method is commonly taken; a review of literature-reported SVE models (Table 1) yielded twenty-two coupled air flow/contaminant transport and removal models [ 7-28], as well as six air flow-only models [29][30][31][32][33][34] based on this approach.…”
Section: Process Performancementioning
confidence: 99%